DESAIN RUSUNAWA DENGAN KONSEP BANGUNAN HEMAT ENERGI DI BUKIT DURI JAKARTA SELATAN - Triana Melani; Anggraeni Dyah Sulistiowati (MAESTRO, 2019)
The large number of people who live in the capital city of Jakarta makes more and more demand for housing for housing, but the capacity of the available land is increasingly limited so it is not enough to meet the needs of shelter. Procurement of flats in Jakarta is urgently needed, especially for middle and lower class people who have been living in settlements that are not livable. South Jakarta as a city whose development is very fast but still lack of awareness of its citizens to create energy-efficient housing. excessive use of electricity makes the building less energy efficient. Therefore, to overcome these problems, it is necessary to have a plan and design to build housing in the city of South Jakarta, such as making energy-efficient Rusunawa, by using the concept of Energy Saving that can create an environment that is environmentally friendly, comfortable while saving energy.